PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK TALK WRITE (TTW) DISERTAI KUIS TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS X SMAN 3 SOLOK SELATAN TAHUN PELAJARAN 2013/2014 - Novia, Rini; Nst, Minora L; Cesaria, Anna (Pendidikan Matematika, 2013)
The high school of students SMAN 3 Solok Selatan have a matter about the lack of Understanding of mathematical concepts. This study aims to determine whether students understanding of mathematical conceps with the aplication of Cooperative Learning Model type Think Talk Write (TTW) accompanied quiz better thanthestudents understanding of mathematical conceps by using convensional learning isthe class X SMAN 3 Solok Selatan 2013/2014. This type of research is experimental Thee study population was a tenth grade the high school of students class X SMAN 3 Solok Selatan. Techniques in sampling is random,which was selected as the experimental class is X.4 and control class is X.3. The instrument used was the ultimate test with indikator understanding of mathematical conceps. Form used is the essay test with a reliabiliti of 0,92. Result of students skill is treated by one person. Obtained P-value = 0,005 is less then the significan level a = 0,05. The resulted in H1 is accepted and it can be concluded that the students understanding of mathematical conceps with the application of Cooperative Learning Model type Think Talk Write (TTW) accompanied quiz better then understanding of the mathematical conceps that students applying conventional learning the high school of students class X SMAN 3 Solok Selatan 2013/2014